Pengelasan kata kerja bahasa Melayu: pendekatan semantik berdasarkan Role and Reference Grammar (RRG) (Jurnal Bahasa, 2008)
Traditionally, verbs are divided into transitive verbs and intransitive verbs. This classification is based on the syntactic characteristic of the verbs. This paper attempts to describe the classification of Malay verbs based on the lexical meaning of verbs. The approach to the depiction of the lexical meaning of verbs which will be adopted is lexical decomposition. This system is based on the distinctions in Aktionsart. Aktionsart is a lexical class to which a verb belongs by virtue of the type of process, state, and so forth, that it designates. Thus this paper will propose a set of syntactic test Ibr determining verbs classes in Malay, with reference to the syntactic test presented in Role and Reference Grammar (RRG).